1998
DOI: 10.1038/sj.leu.2400991
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional rapid ERK1,2 activation is indispensable for proliferation of the growth factor-independent myeloid leukemic cell line KG1

Abstract: While normal hematopoietic progenitor cells are dependent on colony-stimulating factors for in vitro proliferation, myeloid leukemic cells are frequently factor-independent. In this study we investigated several signalling intermediates of the Ras-Erk1,2 pathway which may be involved in the development of growth factor independence. In the growth factor independent cell line KG1, an extremely short activation pattern of Erk1,2 with a maximum at 30 s was observed in response to FBS. In contrast, stimulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…PD98059 has been show to block the proliferation of different cancer cell lines (47)(48)(49) and can also prevent growth of the acute promyelocytic leukemia cell line KG1 (50). However, we found that PD98059 had no significant effects on the proliferation of most of the leukemic cell lines used in this study.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…PD98059 has been show to block the proliferation of different cancer cell lines (47)(48)(49) and can also prevent growth of the acute promyelocytic leukemia cell line KG1 (50). However, we found that PD98059 had no significant effects on the proliferation of most of the leukemic cell lines used in this study.…”
Section: Discussioncontrasting
confidence: 61%
“…Nevertheless, this and other studies (32,46,50) show that variable degrees of ERK activity can be present in leukemias. Whether ERK activation could determine the susceptibility to different therapies or serve as a prognosis marker in myeloid leukemia merits some attention.…”
Section: Discussionmentioning
confidence: 42%
“…Figure 2A) (ERK is not constitutively phosphorylated in KG1A and is not, therefore, not examined here). 18 Cleaved caspase 3 and cleaved PARP increased with increasing inhibitor concentration indicating increased levels of apoptosis ( Figure 2B). These results are consistent with a recent study demonstrating activity of ponatinib against CUX1-FGFR1 transformed Ba/F3 cells.…”
Section: Resultsmentioning
confidence: 97%
“…Aβ treatment can activate the MAPK signaling cascade in acute hippocampal slices as well as primary neurons (Ekinci et al 1999; Rapoport and Ferreira, 2000; Dineley et al 2001). ERK activation is a rapid, transient event with peak activation occurring within 2–5 min and returning to baseline after 15 min (Dabrowski et al 1997; Barge et al 1998; Porras et al 1998), and activity exceeding 1 h after exposure to a stimuli is indicative of sustained kinase activation (Dabrowski et al 1997). Our studies on primary neurons treated with oligomeric Aβ for as little as 5 min to as long as 24 h (only data from 24 h is shown) showed a significant increase in expression of Ras and phosphorylation of ERK only after 6 h of treatment, suggesting that chronic neuronal Aβ exposure elicits sustained MAPK signaling.…”
Section: Discussionmentioning
confidence: 99%